Greater hemodynamic stresses initiate aneurysms on major cerebral arterial bifurcations - Guo, Hao; Liu, Jian-Feng; Li, Cong-Hui; Wang, Ji-Wei; Li, Hui; Gao, Bu-Lang (Frontiers in Neurology, 2023)
Objective To retrospectively investigate the hemodynamic stresses in initiating aneurysm formation on major cerebral arterial bifurcations with computational fluid dynamics (CFD) analysis. Methods The cerebral 3D angiographic data of major cerebral arterial bifurcations of the internal carotid, middle cerebral, anterior cerebral, and basilar arteries in 80 patients harboring bifurcation aneurysms and 80 control subjects with no aneurysms were retrospectively collected for the CFD analysis of hemodynamic stresses associated with aneurysm formation. Results Bifurcation angles at major bifurcations in all patients were significantly positively (P < 0.001) correlated with the age. At the center of direct flow impingement (CDFI) on the bifurcation wall, total pressure was the highest but dropped rapidly toward the branches. Wall shear stress, dynamic pressure, strain rate, and vorticity were lowest at the CDFI but they increased quickly toward the branches. The bifurcation angle was significantly (P < 0.001) enlarged in patients with bifurcation aneurysms than those without them, for all major arterial bifurcations. Most aneurysms leaned toward the smaller arterial branch or the arterial branch that formed a smaller angle with the parent artery, where the hemodynamic stresses increased significantly (P < 0.05), compared with those on the contralateral arterial branch forming a larger angle with the parent artery. Following the aneurysm development, all the hemodynamic stresses on the aneurysm dome decreased significantly (P < 0.001) compared with those at the initiation site on the bifurcation wall after virtual aneurysm removal. With the decrease of bifurcation angles, all the hemodynamic stresses decreased. Conclusion The formation of intracranial aneurysms on major intracranial arterial bifurcations is significantly associated with locally abnormally augmented hemodynamic stresses, which must be reduced.